Land Bank Governance and Agrarian Justice: The Risk of Land Grabbing and State Responsibility in Contemporary Agrarian Reform - Muhammad Dias Saktiawan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
This article critically analyzes the existence of Land Banks in contemporary agrarian reform, placing them within the perspective of agrarian justice and state responsibility. Based on the assumption that land is not merely an economic asset, but rather the basis of life and social justice, this research examines the philosophical foundations, legal construction, and governance and authority of Land Banks, which have the potential to facilitate legally legitimized land grabbing practices. This research uses a normative-critical approach by combining legislative, conceptual, critical-theoretical, and limited comparative approaches. The research findings indicate that the institutional design and authority of the Land Bank reflect a shift in the rationality of agrarian law from a redistribution paradigm to asset management and development interests, which risks obscuring the corrective function of agrarian law. This article emphasizes that state responsibilities under agrarian law must be interpreted substantively, encompassing normative, preventive, protective, and remedial obligations to prevent land grabbing and protect community agrarian rights. These findings contribute to strengthening critical agrarian law discourse by offering a conceptual framework for reassessing the role of the Land Bank to ensure it remains aligned with the principles of agrarian justice and rights protection.